Demographic Change Necessitates Educational Reform and Lifelong Learning - Karl Brenke; Klaus F. Zimmermann (Weekly Report, 2005)
Even though the share of workers retiring prematurely is growing, the average age of the labor force is rising because the younger age groups are contracting and the length of time they spend in education is increasing. And yet the German higher education system is relatively unproductive. While the propensity to study at the college level has increased, for demographic reasons the number of German students studying in Germany is no higher than it was ten years ago. By contrast, the share of foreign students studying in Germany has doubled over the last decade, and more German students are studying abroad. The labor force potential of young people must be better exploited in the future in the sense that they should leave the education system earlier and with improved qualifications. In addition, the process of globalization demands that German universities open their doors even wider to foreign students: first, in the interests of exporting education and, second, as a means to attract highly qualified graduates to Germany. The speed with which knowledge changes, together with the need - and the possibility - to increasingly extend the working life of older workers, necessitates a broader provision of advanced training, within universities as well. There is certainly some degree of willingness to participate in ongoing training among the members of Germany's labor force, but there is also considerable scope for expansion in this regard. However, willingness to engage in continuing education is more prevalent among the younger than the older labor force. Only when the vocational prospects of older workers change will the members of this group show a greater interest in pursuing advanced training and continuing education.
Keywords: 330